Aplikasi Pengenalan Fosil-Fosil Purba Di Museum Purbakala Sangiran Berbasis Android - Setiyarini, Unun, Endah Sudarmilah,.S.T.,M.Eng (2016)
Technological development in the is now not avoided again , various technologies a speedy .One of them , technology smarthphone using android , recent years has the technology android many of the market .Based on it , writer design application the introduction of ancient fosil-fosil in museums ancient android sangiran based , to ease in know and learn to ancient fosil-fosil in ancient sangiran museum , and helping visitors to reach the museum with the guidelines of application to be made .In addition the application can be used as media to introduce ancient sangiran museum .The purpose of this study is to making an application the introduction of fosil-fosil ancient based in museums sangiran android to ease users in access and increase awareness about ancient fosil-fosil there . The results of this research is the application of the introduction of the ancient fossils of Sangiran Archaeological Museum are online, which means it needs an internet connection to use it. Application introduction of ancient fossils of Sangiran Archaeological Museum can be used to help users to pay a visit to the museum, and provide information about the Archeological Museum of Sangiran, like its purpose as a media promotion. Application introduction of ancient fossils of Sangiran Archaeological Museum can be run on a smarthphone with android operating system at least version 4.0 that is Ice Cream Sandwitch. Validity of the test results stated were valid, while on test reliability are categorized on the high reliability that is 0.705. The percentage of the respondents assessment chart shows that high.